2019
DOI: 10.1007/s12011-019-01728-0
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Sulfate in Narrow Range as an In Vitro Anti-HSV-1 Assay

Abstract: This report explains the employing of a combination test of traditional cell culture with a quantitative real-time PCR for assessment of the antiviral effect of zinc sulfate (ZnSO 4 ) on herpes simplex virus (HSV)-infected Vero cells. Our evidence showed that the treatment with 0.3 mM ZnSO 4 strongly inhibited the replication of virus progeny (MOI 0.001) at least 68-fold less. On the other hand, the IC50 demonstrated that the highest activity of ZnSO 4 was at the 0.23 mM concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Although the effect of zinc ion against a wide range of viral pathogens has been proven since 1967, the utilization of it as a viral medication has been restricted as it is quite toxic for host cells (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effect of zinc ion against a wide range of viral pathogens has been proven since 1967, the utilization of it as a viral medication has been restricted as it is quite toxic for host cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…The extracted RNA was then subjected to reverse transcription using the cDNA Synthesis Kit (Bio fact, Korea). The late gene UL27 (encoding glycoprotein gB) were determined by using Rotor-Gene Q instrument in a thermal pro le of 95 °C for 2 min (1 cycle), 95 °C for 30 s, and 60 °C for 15 s (35 cycles, respectively) (29). The transcription levels of total RNA in each sample were normalized against the GAPDH gene.…”
Section: *Viral Titer Formulamentioning
confidence: 99%
“…In vitro experiments have shown that zinc impairs viral replication and has beneficial effects on RNA viruses like coronavirus. Zinc supplementation in children documented to be deficient has been shown to decrease mortality, although data are inconsistent 49,50 . No consistent data show zinc supplementation in intensive care patients to be of benefit 51 .…”
Section: Potential Nutrition Interventions Based On Theory Extrapolamentioning
confidence: 99%
“…Singh et al, in their randomized, double-blind, placebo-controlled trial study, reported the ameliorative effect of zinc in reducing the duration of colds [ 79 ]. Some other studies have indicated the antiviral activity of zinc against various viruses including influenza [ 80 ], rhinovirus, herpes virus, respiratory syncytial virus and transmissible gastroenteritis virus [ 81 ]. Such immunomodulatory and antiviral properties of zinc, highlights its potential role as a supportive agent in the treatment of COVID-19.…”
Section: The Roles Of Zinc In the Inhibition Of Acute Respiratory Distress Syndrome (Ards)mentioning
confidence: 99%